SISTEM INFORMASI KEPEGAWAIAN FAKULTAS TEKNIK UNIVERSITAS HALU OLEO SUB-SISTEM UTILITY DAN PENGGAJIAN - Muhammad Ichwan Utari; Ika Purwanti Ningrum; Muh. Yamin (semanTIK, 2016)
Currently the employee and financial data management in the Faculty of Engineering, Halu Oleo University, Southeast Sulawesi already using computer technology, but overall employee data is entered manually. In addition, data that has been entered in the officialdom service and finance can not be viewed in real-time by an employee of the Faculty of Engineering who are not in the field. Based on these problems, the authors feel need to be made an Human Resource Development Faculty of Engineering, Halu Oleo University. The importance of this system to the processing of employee data can be focused and efficient. In addition, enables the user to enter personal data anytime and anywhere. The test results, the system displays the calculation table details the net salary of employees who relied on periodic salary increases, allowances, and discounts, according to the rule system that applies to the finance department. In this system, salaries are processed only the salaries of employees with employment status of civil servants. In addition, all operations in the system has been running well. Keywords—Information Systems, Periodically Salary Increases, The Net Salary.